Pengaruh Inovasi Layanan dan Efisiensi Operasional Terhadap Kepuasan Pelanggan Berimplikasi Loyalitas Terhadap PT Balancia Ship Agensi - Nur Jalilah; Agung Kwartama; Marihot Simanjuntak (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Business competition in the sea transportation sector requires companies to continue to innovate and improve operational efficiency in order to maintain customer satisfaction and loyalty. This study aims to provide the influence of service innovation and operational efficiency on customer satisfaction and remind him of customer loyalty at PT Balancia Ship Agency. Research uses a quantitative approach with a survey method through questionnaires distributed to company customers. The analysis results show that both service innovations and operational efficiency have a positive and significant effect on customer satisfaction. Customer satisfaction is also proven to mediate the relationship between service innovation and operational efficiency of customer loyalty. This finding shows that efficient service and operational improvement strategies are very important in building long term relationships with customers, while increasing the competitiveness of the company in the shipping industry.